2019
DOI: 10.1021/acsomega.9b03190
|View full text |Cite
|
Sign up to set email alerts
|

Computing Investigations of Molecular and Atomic Vibrations of Ice IX

Abstract: The normal modes of ice IX were investigated using the CASTEP code package, which is based on density functional theory. We found that the translational modes could be divided into three categories: four-bond vibrations, which possessed the highest energy; two-bond vibrations, which possessed the medium energy; and cluster vibrations with the lowest energy. The former two categories represent monomers vibrating against neighbors and present as two distinct peaks in many ice phases recorded in inelastic neutron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
3
0
1
Order By: Relevance
“…We have reviewed the vibrational normal modes of ice XV and clarified the physical aspects of its exotic vibrational modes . The distributions of vibrational modes in ice XV are similar to those we have determined in our previous series of studies, such as ice VII and VIII, and the hydrogen-bonding modes in the translational band also obey the theory of two types of hydrogen bonds. Based on a successful investigation of ice XV, in this study, we constructed an ice VI supercell, explored its atomic and molecular vibrational modes, and compared these modes with those of ice XV. A comparative analysis was also reported in the meaning of an experimental method.…”
Section: Introductionsupporting
confidence: 57%
“…We have reviewed the vibrational normal modes of ice XV and clarified the physical aspects of its exotic vibrational modes . The distributions of vibrational modes in ice XV are similar to those we have determined in our previous series of studies, such as ice VII and VIII, and the hydrogen-bonding modes in the translational band also obey the theory of two types of hydrogen bonds. Based on a successful investigation of ice XV, in this study, we constructed an ice VI supercell, explored its atomic and molecular vibrational modes, and compared these modes with those of ice XV. A comparative analysis was also reported in the meaning of an experimental method.…”
Section: Introductionsupporting
confidence: 57%
“…一般而言, 随着压强的增加, 氢键 键长变短, 氢键强度应增强. 但冰VIII和冰XV [142] 是个特殊的例子. 这归因于它们特殊的结构, 冰 VIII和冰XV皆是由两个子晶格相互套构而成的, (单位: cm -1 ), 结构优化密度(单位: g/cm -3 ) Table 2.…”
Section: 冰Ic理想模型中的两类本征振动unclassified
“…The PDOS of ices III and IX are consistent with their respective INS spectra. In the translation band, it is clear that the two typical HB peaks are at approximately 200 cm −1 and 300 cm −1 for ice IX [20], whereas there is a flat vibrational band for ice III in the same region. To analyze the HBs of ice III, we first introduce the theory of two kinds of intrinsic HB vibrational modes in ice.…”
Section: Resultsmentioning
confidence: 98%
“…Two kinds of intrinsic HB vibrational modes, denoted two-bond and four-bond modes, were found for the ideal ice Ic [21]. A series of investigations of the ice phases has revealed that this is a general rule for the ice family and may successfully explain their far-IR band [18][19][20]. In the present study, we theoretically analyzed the vibrational modes in the translation band to identify the characteristic HB vibrations of ice III in comparison with those of the H-ordered ice IX.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation